2018
DOI: 10.1111/1747-0080.12461
|View full text |Cite
|
Sign up to set email alerts
|

Health‐e mums: Evaluating a smartphone app design for diabetes prevention in women with previous gestational diabetes

Abstract: A user-centred approach was taken to develop a diabetes prevention program app for women with prior gestational diabetes. Women were predominantly satisfied with the overall app design, how it functioned and what the user experience would be like when fully developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(71 citation statements)
references
References 41 publications
(70 reference statements)
2
69
0
Order By: Relevance
“…Of the included studies, four were conducted in Australia (3133, 37), three in the USA (3436), one in England (22), and one in Bangladesh (38). Five studies conducted interviews (22, 31, 32, 36, 37), two conducted focus groups (33, 35), one conducted a survey (34), and one conducted a combination of surveys, focus groups, and interviews (38). In all studies, participants were within the first year after birth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the included studies, four were conducted in Australia (3133, 37), three in the USA (3436), one in England (22), and one in Bangladesh (38). Five studies conducted interviews (22, 31, 32, 36, 37), two conducted focus groups (33, 35), one conducted a survey (34), and one conducted a combination of surveys, focus groups, and interviews (38). In all studies, participants were within the first year after birth.…”
Section: Resultsmentioning
confidence: 99%
“…In all studies, participants were within the first year after birth. Delivery modes of the DHIs in these studies included websites (22, 31, 34, 36), social media (Facebook) (31), smartphone applications (31, 33, 35), telephone counseling (31, 32, 38), group blog (31), text message (34, 36), voice message (38), video (22, 34, 37), and email (34, 36). Most studies utilized more than one delivery mode in the DHIs.…”
Section: Resultsmentioning
confidence: 99%
“…In this issue, O'Reilly et al conducted a series of focus groups to evaluate a pilot diabetes prevention smartphone app for women with a history of GDM. Women found the app more accessible and useful compared to traditional printed health information and the app made it easier for the women to initiate changes in lifestyle health behaviours, and to regularly screen for type 2 diabetes . In another study, McCampley et al reported the benefits of electronic medical records for improving the delivery of dietetics services in an Australian hospital.…”
Section: Ehealthmentioning
confidence: 99%
“…26,27 For example, during the post-partum period, women find it difficult to seek health advice in-person due to a lack of time and access to childcare. 28 In this issue, O'Reilly et al 29 conducted a series of focus groups to evaluate a pilot diabetes prevention smartphone app for women with a history of GDM. Women found the app more accessible and useful compared to traditional printed health information and the app made it easier for the women to initiate changes in lifestyle health behaviours, and to regularly screen for type 2 diabetes.…”
Section: E Healthmentioning
confidence: 99%
See 1 more Smart Citation